OPTIMIZATION OF CRANIOPHARYNGIOMAS SURGICAL TREATMENT THROUGH INTRAOPERATIVE MONITORING OF VISUAL EVOKED POTENTIALS - Uygun U. Altybayev; Alisher M. Sultanov; Jaxongir Z. Yo’ldoshev; Gulrux T. Achilova (Central Asian Journal of Medicine, 2025)
This study explores the optimization of surgical treatment for craniopharyngiomas through intraoperative monitoring of visual evoked potentials (VEP). The aim was to enhance the safety and effectiveness of tumor removal by providing an objective assessment of the visual system’s functional state during surgery, particularly in cases where the tumor is in close proximity to the optic nerves and chiasm. A total of 59 patients were divided into two groups: a control group that underwent standard surgical treatment and a main group in which intraoperative VEP monitoring was additionally applied. Comparative analysis demonstrated that VEP monitoring significantly improved visual acuity and field expansion, reduced postoperative visual impairments, and increased the precision of tumor resection. The findings confirm the effectiveness of intraoperative VEP monitoring in craniopharyngioma surgery, supporting its broader use to minimize neurological complications and improve functional outcomes for patients.